2008
DOI: 10.1152/physiolgenomics.00086.2007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of longitudinal leukocyte gene expression after burn injury or trauma-hemorrhage in mice

Abstract: A primary objective of the large collaborative project entitled “Inflammation and the Host Response to Injury” was to identify leukocyte genes that are differentially expressed after two different types of injury in mouse models and to test the hypothesis that both forms of injury would induce similar changes in gene expression. We report here the genes that are expressed in white blood cells (WBCs) and in splenocytes at 2 h, 1 day, 3 days, and 7 days after burn and sham injury or trauma-hemorrhage (T-H) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…After severe trauma, a ‘genetic storm’ and functional reprioritizing of leukocytes have been described 22 that seem in other studies to be unique to each injury pattern 23 . Overall, the cellular translation results in largely balanced pro-inflammatory and anti-inflammatory protective effects mediated by targeted chemotaxis, cytokine release (with the systemic appearance of, for example, IL-6, IL-8, IL-1Ra and IL-10), the generation of reactive oxygen species (ROS), phagocytosis, the formation of neutrophil extracellular traps (NETs) and the killing of bacteria 6,2428 .…”
Section: Protective and Harmful Innate Immune Responses To Traumamentioning
confidence: 95%
“…After severe trauma, a ‘genetic storm’ and functional reprioritizing of leukocytes have been described 22 that seem in other studies to be unique to each injury pattern 23 . Overall, the cellular translation results in largely balanced pro-inflammatory and anti-inflammatory protective effects mediated by targeted chemotaxis, cytokine release (with the systemic appearance of, for example, IL-6, IL-8, IL-1Ra and IL-10), the generation of reactive oxygen species (ROS), phagocytosis, the formation of neutrophil extracellular traps (NETs) and the killing of bacteria 6,2428 .…”
Section: Protective and Harmful Innate Immune Responses To Traumamentioning
confidence: 95%
“…It must be noted that an oral communication by one of the PNAS co-authors indicated that reanalysis of genomic responses in a more narrow PMN population did not markedly improve the overall correlation (20), although a peer-reviewed publication of such a reanalysis has not yet been reported. The risks of imprecise comparison of genomic responses in circulating white blood cells (WBC) are not solely restricted to mouse versus human studies; earlier GLUE GRANT-based reports that analyzed various inflammation/injury scenarios using only mouse models, voiced identical concerns (49;50). Analyses of gene expression in discrete leukocyte subsets are certainly warranted as they provide more precise information regarding individual activation patterns in injury and/or infection.…”
Section: Lost In Translation: What Does the Pnas Study Really Say?mentioning
confidence: 99%
“…It has been suggested that in systemic inflammatory response syndrome (SIRS) and/or infection, compartmentalized synthesis and release of inflammatory cytokines are equally important (63-65) and that cells other than leukocytes may be responsible for morbidity and mortality in trauma (61), inflammatory shock (66), endotoxemia (67-69) and/or infection (70). Studies have also shown that peripheral blood cells fail to reflect what occurs in the tissue fixed cells within the same or different organs (30;49;50;71;72). Furthermore, the concept of compartmentalization pertains to coexistence of differential (and often contrasting) responses that depend on the specific location of the immune-competent machinery and this notion has been supported by numerous preclinical studies.…”
Section: Lost In Translation: What Does the Pnas Study Really Say?mentioning
confidence: 99%
“…The Inflammation and Host Response to Injury, Large Scale Collaborative Research Program has completed multiple studies on the genomic responses to systemic inflammation in patients and human volunteers as well as murine models (14)(15)(16)(17)(18). These datasets include genome-wide expression analysis on white blood cells obtained from serial blood draws in 167 patients up to 28 d after severe blunt trauma (15), 244 patients up to 1 y after burn injury, and 4 healthy humans for 24 h after administration of low-dose bacterial endotoxin (14) and expression analysis on analogous samples from well-established mouse models of trauma, burns, and endotoxemia (16 treated and 16 controls per model) (16)(17)(18).…”
mentioning
confidence: 99%
“…These datasets include genome-wide expression analysis on white blood cells obtained from serial blood draws in 167 patients up to 28 d after severe blunt trauma (15), 244 patients up to 1 y after burn injury, and 4 healthy humans for 24 h after administration of low-dose bacterial endotoxin (14) and expression analysis on analogous samples from well-established mouse models of trauma, burns, and endotoxemia (16 treated and 16 controls per model) (16)(17)(18). In humans, severe inflammatory stress produces a genomic storm affecting all major cellular functions and pathways (15) and therefore, provided sufficient perturbations to allow comparisons between the genes in the human conditions and their orthologs in the murine models.…”
mentioning
confidence: 99%